Chitinase-like1 Plays a Role in Stalk Tensile Strength in Maize. Issue 3 (6th September 2019) - Jiao, Shuping; Hazebroek, Jan P.; Chamberlin, Mark A.; Perkins, Mark; Sandhu, Ajay S.; Gupta, Rajeev; Simcox, Kevin D.; Yinghong, Li; Prall, Alan; Heetland, Lynn; Meeley, Robert B.; Multani, Dilbag S.
Abstract : Phenotypic, histological, and biochemical characterization of loss-of-function mutant and overexpression lines of Chitinase-like1 support a role for ZmCtl1 in tensile strength enhancement in maize. Abstract: Stalk lodging in maize ( Zea mays ) causes significant yield losses due to breaking of stalk tissue below the ear node before harvest. Here, we identified the maize brittle stalk4 ( bk4 ) mutant in a Mutator F2 population. This mutant was characterized by highly brittle aerial parts that broke easily from mechanical disturbance or in high-wind conditions. The bk4 plants displayed a reduction in average stalk diameter and mechanical strength, dwarf stature, senescence at leaf tips, and semisterility of pollen. Histological studies demonstrated a reduction in lignin staining of cells in the bk4 mutant leaves and stalk, and deformation of vascular bundles in the stalk resulting in the loss of xylem and phloem tissues. Biochemical characterization showed a significant reduction in p -coumaric acid, Glc, Man, and cellulose contents. The candidate gene responsible for bk4 phenotype is Chitinase-like1 protein ( Ctl1 ), which is expressed at its highest levels in elongated internodes. Expression levels of secondary cell wall cellulose synthase genes ( CesA ) in the bk4 single mutant, and phenotypic observations in double mutants combining bk4 with bk2 or null alleles for two CesA genes, confirmed interaction of ZmCtl1 with CesA genes. Overexpression of ZmCtl1 enhanced mechanical stalk strength without affecting plant stature, senescence, or fertility. Biochemical characterization of ZmCtl1 overexpressing lines supported a role for ZmCtl1 in tensile strength enhancement. Conserved identity of CTL1 peptides across plant species and analysis of Arabidopsis ( Arabidopsis thaliana ) ctl1-1 ctl2-1 double mutants indicated that Ctl1 might have a conserved role in plants.